On a necessary condition for L^p (0 < p < 1)-convergence (upper boundedness) of trigonometric series - Krasniqi, Xh.Z. (Carpathian Mathematical Publications, 2015)
In this paper we prove that the condition _k=[n2] ^2nλ _k(p)(|n-k|+1)^2-p =o(1) (=O(1) ), is a necessary condition for the L^p (0<p<1)-convergence (upper boundedness) of a trigonometric series. Precisely, the results extend some results of A. S. Belov.